Notes on Eotrechus Kirkaldy, 1902 (Heteroptera: Gerridae), with descriptions of two new species - Tran, Anh Duc; Zettel, Herbert (Zootaxa, 2006)
Two new species of Eotrechus are described: Eotrechus pilicaudatus sp.n. from northeastern India and Eotrechus luaae sp.n. from China (Hainan Island); both are closely related to Eotrechus pingae Andersen, 1998 from China (Guangdong). The occurence of Eotrechus kalidasa Kirkaldy, 1902 in northeastern India is confirmed. Eotrechus terrestris Andersen, 1982 is recorded from Nepal for the first time.